ANALISIS DINAMIKA SOSIAL EKONOMI DAN KELEMBAGAAN UNTUK PENINGKATAN PERAN PETANI DALAM PENGELOLAAN IRIGASI BATANG TABIK KECAMATAN LUAK KABUPATEN LIMA PULUH KOTA - Siska Handayani; Oktorinda Ekasa Putra (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2022)
Irrigation management is strongly influenced by socio-economic conditions and community institutions that use and are located in the Irrigation Area (IA). In Batang Tabik IA, although the water is quite large upstream, downstream the water is very small, even some of the farmers' land cannot be planted with rice, thereby reducing land productivity and farmers' income. In this condition, the role of farmers in irrigation management is very much needed to meet the water needs for their farming. This study attempts to describe and analyze the socio-economic dynamics and farmer institutions in Batang Tabik IA. This analysis can be a guide for efforts to increase the role of farmers in irrigation management. This study used a case study method with 84 samples of farmers from Nagari Sungai Kamuyang, Andaleh and Mungo. This research shows that mutual cooperation and irrigation management in Batang Tabik are still lacking, which can be seen from the large amount of garbage found in the canal and illegal collection in the canal. The average income of farmers in 1 planting season for one ha of land is Rp. 8,325,000 to 12,465,000. The majority of Water-Using Farmers' Association (WUFA) in Batang Tabik are less active and have not collected water fees, besides that (WUFA) do not have AD/ART, programs, work plans and  operations. It is necessary to enforce regulations regarding waste and illegal water collection. In addition, efforts to improve irrigation techniques, revitalization and (WUFA) development are needed to increase the role of farmers